CORRELATION OF ANTHROPOMETRY AND BODY COMPOSITION IN WOMEN WITH AGE - Dewi, Andriana Kumawa; Setiawan, Fiona Valencia; Firmansyah, Yohanes (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tarumanagara, 2024)
Background: Ageing has been associated with molecular and physiological changes, which lead to a change in body composition, a reduction in lean mass, an increase in fat mass, and a reduction in basal metabolic rate. These further increase vulnerability to obesity, metabolic disorders, and their complications, particularly in women. Objectives: This study investigates the relationship between anthropometric parameters and body composition with age in women to identify changes that occur as age increases. Method: A cross-sectional study by purposive sampling was carried out on 144 women aged 18 years and above. Anthropometric data such as weight, height, and circumferences were measured alongside body composition parameters like total body fat, visceral fat, and skeletal muscle mass. BMR (Basal Metabolic Rate) was determined by the Omron Karada Scan HBF 375, while its correlations were studied using Pearson's correlation. Results: There were significant correlations of age with major body composition parameters with aging. There was an increase in total body fat (r = 0.249, p = 0.003) and a decrease in skeletal muscle mass (r = -0.206, p = 0.013), contributing to a decline in BMR (r = -0.231, p = 0.005). Calf circumference was also significantly negatively correlated with age: r = -0.201, p = 0.015. Conclusion: The most significant influences of aging are on body composition and BMR due to increased fat mass and reduced skeletal muscle reduction that lower metabolic activity. This condition increases the risk of metabolic disorders, regular body composition, and health education monitoring.